PENGARUH LIFESTYLE, WORD OF MOUTH DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN MS. GLOW PADA MAHASISWA UNMUH PONOROGO - Anggun Voga Nitissia; Heri Wijayanto; Naning Kristiyana (Gapenas Publisher, 2022)
This study aims to determine the effect of Lifestyle, Word Of Mouth and Product Knowledge, either partially or jointly on MS Purchase Decisions. Glow on Unmuh Ponorogo Students. This study uses quantitative methods. There are 96 respondents. sampling using purposive sampling technique with a questionnaire as a data collection tool. From the results of data analysis, it was found that Lifestyle, Word Of Mouth and Product Knowledge partially and simultaneously/simultaneously influence